(untitled) (Business & Management Studies: An International Journal, 2024)
This study examines the relationship between carbon emissions and financial constraints, exploring the moderating impact of ownership. We employ a large sample from 24 developed countries for the years spanning from 2002 to 2022. Our sample is composed of 20,774 company-specific observations from 2632 unique companies. We use panel data estimation methodology with the inclusion of fixed effects. Our analysis reveals a significant positive association between carbon emissions and financial constraints. The results indicate that firms with higher carbon emissions experience more significant financial constraints. Moreover, we provide novel evidence that ownership structure has a moderating impact, such that the positive effects of carbon emissions on financial constraints are higher for firms with more institutional and foreign ownership. Conversely, state ownership has a negative moderating impact, suggesting that the positive influence of carbon emissions on financial constraints is less for corporations with higher state ownership. Overall, our findings suggest that environmental performance is an essential factor influencing a firm’s financial constraints, and the firm’s ownership structure moderates this effect.